Hepatitis B virus genotype and subgenotype prevalence and distribution in Montenegro. Issue 5 (24th February 2015) - Vratnica, Zoran; Zehender, Gianguglielmo; Ebranati, Erika; Sorrentino, Chiara; Lai, Alessia; Vujošević, Danijela; Veo, Carla; Presti, Alessandra Lo; Cella, Eleonora; Giovanetti, Marta; Laušević, Dragan; Galli, Massimo; et al.
Abstract : The Mediterranean area and the Balkans in particular show the highest level of genetic heterogeneity of HBV in Europe. Data about the circulation of HBV genotypes in Montenegro are lacking. It was studied the prevalence and distribution of HBV genot/subgenotypes in a total of 150 HBV infected patients living in Montenegro. Phylogenetic analysis of 136 successfully amplified P sequences showed a high degree of genetic heterogeneity of HBV in Montenegro. Subgenotype D2 (36.8%) and D3 (32.3%) were the most prevalent, followed by genotype A (subgenotype A2 in all of the cases‐19.8%). Eight patients were infected with recombinant strains. HBV‐D1 which is the most spread HBV subgenotype in the south‐eastern Mediterranean countries, seems to be relatively rare in Montenegro, suggesting a penetration of HBV more probably from North‐East or West than from Eastern Mediterranean countries. The relatively different prevalence of D3 and A2 among subjects infected through sexual route, seems to confirm the association of these subgenotypes with different route of transmissions (mainly parenteral for D3 and mainly sexual for A2) even in Montenegro. The low prevalence of D2 among children and its absence in perinatal transmission, suggests that this subgenotype circulated prevalently in the past. If this is due to changes in the most prevalent way of transmission and in the recent different contacts of Montenegro with other European countries, it remains to be established by other larger studies. J. Med. Virol. 87:807–813, 2015 . © 2015 Wiley Periodicals, Inc.